PELAKSANAAN SUPERVISI AKADEMIK PENGAWAS SEKOLAH SEBAGAI UPAYA PENINGKATAN PROFESIONALISME GURU - Messi, Messi; Anggita Sari, Wiwin; Murniyati, Murniyati (Graduate Program Magister Manajemen Pendidikan, 2018)
Academic supervision is an activity planned to help teachers in the learning process in order to improve students’ learning outcomes. This study aimed at investigating the supervision of school’s supervisor in improving the professionalism of teachers and improve the quality of education at SMP Negeri 44 Palembang. The type of this research is qualitative and the data were obtained by observation, documentation and interview. The results of this study (1) supervision conducted by applying the official approach, partners, and kinship, and the techniques developed by supervisors in implementing academic supervision vary considerably; (2) supervisory obstacles in carrying out academic supervision is the number of teachers were too many, however it only had limited time; (3) the implementation of general academic supervision is good enough and able to carry out its duties and functions properly; (4) aspects that have been targeted by the supervision of school’s supervisors are still limited, not all aspects of academic supervision; (5) the frequency of visits by school’s supervisors in conducting academic supervision is considered lack because it is not evenly distributed; teachers receive class visits by supervisors; and (6) efforts made by supervisors in carrying out academic supervision at SMP Negeri 44 Palembang have not been optimal in providing guidance to teachers.